ANALISIS LAPORAN KEUANGAN UNTUK MENILAI PRESTASI PERUSAHAAN MANUFAKTUR SUB SEKTOR SEMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Melvi Yansi (UNIVED Press, 2017)
Melvi Yansi: This study aims to better know the performance of cement companies were assessed from the financial statements, by taking samples of the two cement companies listed on stock exchanges of Indonesia, namely PT. Indocement Tunggal Perkasa Tbk and PT. Holcim, Tbk from 2014 until 2015. This research is comparative, according to four financial ratios may indicate that the financial performance. Indocement Tunggal Perkasa, Tbk is good enough only for the activity ratio and ROE, and ROI are still not good, while financial performance. Holcim, respectively Tbk unfavorable. PT. Indocement Tunggal Perkasa, Tbk expected to be able to sustain the financial performance of existing and further enhanced in the utilization of current assets, whereas for PT. Holcim, Tbk to be able to improve the financial performance of existing again with lebik better cash management company that will be used to pay liabilities of the company.Key Words: Financial Statements, Financial Ratios.